2018
DOI: 10.1111/ele.13175
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees

Abstract: Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
93
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 56 publications
13
93
0
1
Order By: Relevance
“…However, indirect effects of temperature on biomass exceeded those of direct effects and suggested that biomass increased with increasing temperature, as found for marine fish communities (Duffy et al., 2016). This suggests that available energy limits fish species and functional diversity in stream systems, as for many other taxonomic groups and ecological systems (Chu et al., 2018; Clarke & Gaston, 2006; Field et al., 2009; Hawkins et al., 2003; Swenson et al., 2012). One potential mechanism that might explain the contrasting direct and indirect effects of temperature on biomass might be the observed inverse relationship between temperature and body size (Blanchet et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, indirect effects of temperature on biomass exceeded those of direct effects and suggested that biomass increased with increasing temperature, as found for marine fish communities (Duffy et al., 2016). This suggests that available energy limits fish species and functional diversity in stream systems, as for many other taxonomic groups and ecological systems (Chu et al., 2018; Clarke & Gaston, 2006; Field et al., 2009; Hawkins et al., 2003; Swenson et al., 2012). One potential mechanism that might explain the contrasting direct and indirect effects of temperature on biomass might be the observed inverse relationship between temperature and body size (Blanchet et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that environmental factors have direct effects related to increasing plant community species richness and abundance. Precipitation has been reported to promote the richness of trees and shrubs, and increasing MAT elevated the richness of shrubs in subalpine mountains as well as grasslands (Chu et al, ; Lin, Xia, & Wan, ; Xiong et al, ). The results from the SEMs showed that MAT may decrease the tree canopy and indirectly inhibit tree diversity (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall responses to climate change are primarily driven by direct effects, suggesting that the response of dominant/single species to climate change may be adequate for forecasting the impacts of climate change within specific communities. The size of the indirect effects also depends on the size of the direct effects experienced by species in the community (Chu et al, ). For the differences in the direct and indirect responses of trees and shrubs to environmental factors, ecological niche differences may influence the magnitude of indirect effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic theory proposes that higher temperature results in higher metabolic rates and biochemical processes (Brown, Gillooly, Allen, Savage, & West, 2004), exponentially increasing species mutation and speciation, and finally elevating species numbers (Brown, 2014). This relationship between temperature and biodiversity has been intensively explored in forests for below‐ground microbial communities, showing better predictions in microbial biodiversity and spatial scaling rates than other environmental variables (e.g., pH; Deng et al., 2018;Wu et al., 2018;Zhou et al., 2016), and temperature was also shown to be the important predictor in shaping plant distribution and diversity (Chu et al., 2019;Peters et al., 2016;Rice et al., 2019). In addition, as circumneutral pH (close to neutral pH) and adequate water content provide suitable conditions for a majority of organisms to colonize and reproduce, edaphic pH and water availability (precipitation) are also important variables in shaping community structures and components for both above‐ and below‐ground organisms (Ratcliffe et al., 2017;Rice et al., 2019;Toledo et al., 2011;Zeppel, Wilks, & Lewis, 2014;Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%